2015
DOI: 10.1093/jat/bkv060
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer Profiling of Methamphetamine in White Crystal and Tablet Forms (Ma Old) Using LC–MS-MS

Abstract: At the global level, seizures of crystalline methamphetamine (MA) and MA tablets have risen to a new high, indicating that the substance is an imminent threat. MA enantiomer profiling was a useful tool to investigate the prevalence of MA abuse, the intrinsic characteristics of the seized samples and the trends of precursors. In this work, the distribution of enantiomers in clandestine MA crystals and tablets seized mainly in the Yangtze River Delta region, China, from 2008 to 2014 were identified. The MA sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
5
16
0
Order By: Relevance
“…Keeping this in mind, the measured urine samples from suspected MA abusers can be classified into three groups according to the observed stereoisomeric profiles of AM and the assumed composition of the consumed MA: I) only S-AM present, this indicates misuse of pure S-MA; II) R/S ratios between 0.01 and 0.07 or R-AM concentrations < LLOQ, this might be due to intake of S-MA containing small amounts of R-MA; III) R/S ratios between 0.14 and 0.47, consumption of racemic MA. This classification is supported by the findings reported by Li et al [24], Nagai et al [39] and Wang et al [40].…”
Section: Proof Of Applicabilitysupporting
confidence: 87%
“…Keeping this in mind, the measured urine samples from suspected MA abusers can be classified into three groups according to the observed stereoisomeric profiles of AM and the assumed composition of the consumed MA: I) only S-AM present, this indicates misuse of pure S-MA; II) R/S ratios between 0.01 and 0.07 or R-AM concentrations < LLOQ, this might be due to intake of S-MA containing small amounts of R-MA; III) R/S ratios between 0.14 and 0.47, consumption of racemic MA. This classification is supported by the findings reported by Li et al [24], Nagai et al [39] and Wang et al [40].…”
Section: Proof Of Applicabilitysupporting
confidence: 87%
“…The majority of the seized crystals there also contained pure (S)-methamphetamine, although different fractions of pure (R)-methamphetamine and racemic and non-racemic mixtures were also found. [32][33][34][35][36][37][38] Two of these studies observed a decreasing trend in seizures of the more potent (S)-enantiomer. 32,33 The latter was also observed in an American study from 2005 to 2012, where, in addition to pure (S)-methamphetamine, mainly nonracemic mixtures were found.…”
Section: Discussionmentioning
confidence: 99%
“…Münster‐Müller et al describes a novel stable isotope analysis and impurity‐profiling workflow, using the SCRAs MDMB‐CHMICA (2) and Cumyl‐5F‐PINACA [1‐(5‐fluoropentyl)‐ N ‐(2‐phenylpropan‐2‐yl)‐1 H ‐indazole‐3‐carboxamide] (9) , for the detection of synthesis precursor/by‐product impurities in seized herbal materials and potential source attribution 38–41 . Chiral profiling has been applied previously to illicitly produced drugs including amphetamine and methamphetamine for intelligence purposes, 42–44 although the methodology is rarely routinely employed in forensic drug testing laboratories. We suggest that chiral profiling could be applied to chiral valinate and tert ‐leucinate SCRAs in addition to stable isotopic and impurity profiling; however, the potential utility of such chiral profiling is currently unknown as, to date, there have been no large‐scale studies to determine the variation of enantiopurity of these SCRAs in seized samples.…”
Section: Introductionmentioning
confidence: 99%